Error estimates for quasistatic global elastic correction and linear kinematic hardening material - Lang, Holger; Dreßler, Klaus; Pinnau, René (2006)
We consider in this paper the quasistatic boundary problems of linear elas- ticity and nonlinear elastplasticity with linear kinematic hardening material. We derive expressions and estimates for the difference of the solutions (i.e. the stress, the strain and the displacement) of both models. Further, we study the error between the elastoplastic solution and the solution of a postprocessing method, that corrects the solution of the linear elastic problem in order to approximate the elastoplastic model.
UnivIS-Import:2016-06-30:Pub.2006.tech.FT.ltd.errore
Keywords: Elastic BVP; elastoplastic BVP; variational inequalities; rate-independency; hysteresis; linear kinematic hardening; stop- and play-operator